2021
DOI: 10.1055/a-1490-0434
|View full text |Cite
|
Sign up to set email alerts
|

Digital single-operator cholangioscope for endoscopic retrograde appendicitis therapy

Abstract: Background This study aimed to investigate the diagnostic and therapeutic value of a digital single-operator cholangioscope (SOC) system for endoscopic management of acute appendicitis. Methods 14 patients with acute uncomplicated simple or supportive appendicitis were evaluated between November 2018 and September 2020. The diagnosis of acute appendicitis was confirmed by direct colonoscopy imaging and cholangioscope. The success rate of digital SOC-assisted endoscopic retrograde appendicitis therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Because the shape and size of the appendix varies greatly, it is often challenging to reliably diagnose acute appendicitis with CT and abdominal ultrasound resulting in high negative appendectomy rates. [8,17,19,[26][27][28][29] Several studies have demonstrated that endoscopy combined with appendiceal cavity imaging obtained with ultrasound or X-ray can accurately diagnose acute appendicitis. [10,11,18] [19] The technical success and clinical success of ERAT in our meta-analysis was 99.36% and 99.29% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the shape and size of the appendix varies greatly, it is often challenging to reliably diagnose acute appendicitis with CT and abdominal ultrasound resulting in high negative appendectomy rates. [8,17,19,[26][27][28][29] Several studies have demonstrated that endoscopy combined with appendiceal cavity imaging obtained with ultrasound or X-ray can accurately diagnose acute appendicitis. [10,11,18] [19] The technical success and clinical success of ERAT in our meta-analysis was 99.36% and 99.29% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[8,17,19,[26][27][28][29] Several studies have demonstrated that endoscopy combined with appendiceal cavity imaging obtained with ultrasound or X-ray can accurately diagnose acute appendicitis. [10,11,18] [19] The technical success and clinical success of ERAT in our meta-analysis was 99.36% and 99.29% respectively. In a recent study, ERAT was directly compared to antibiotic therapy alone in children with acute uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
As endoscopy fellows, each of us has been taught that the identification of the appendiceal orifice is the goal of colonoscope progression, ensuring examination of the entire colon. In this issue of Endoscopy, Kong et al push the boundaries and propose examination of the appendiceal lumen with a single-operator cholangioscope (SOC) to provide tailored endoscopic retrograde appendicitis therapy (ERAT) [1]. This new application of an SOC is adapted from the fluoroscopic-guided ERAT technique, a minimally invasive treatment first described in 2012 [2].
…”
mentioning
confidence: 99%
“…Endoscopic transcecal appendectomy eliminates lesions both around the orifice and inside the lumen of the appendix, whereas traditional appendectomy is limited to polyps within the lumen of the appendix. Kong et al reported the endoscopic management of appendicitis using a single-operator cholangioscopy system, which allowed detailed examination of the entire appendiceal cavity during colonoscopy [6]. Use of a single-operator cholangioscope or ultrafine endoscope can detect the presence of polyps inside the appendiceal lumen and help to decide the best strategy for management to avoid complications, as well as any extra financial burden on the patients.…”
mentioning
confidence: 99%